Determinants of Regional Owned Rural Banks Efficiency Level in Indonesia - Irsyad Sirajuddin Bintar Madya; Ghozali Maskie; Nurul Badriyah (Journal of International Conference Proceedings (JICP), 2022)
The efficiency level of regional owned rural banks is one of the determinants in measuring financial performance each year. In term of local government, the measurement of the level of efficiency can be used in determining strategic policies for the development of regional owned rural banks, especially in capital participation and collaboration with fintech lending. Measuring the level of efficiency with input and output variables with 160 regional owned rural banks in Indonesia in 2020 by purposive sampling with the Data Envelopment Analysis (DEA) method, 66 regional owned rural banks are found in efficient conditions. Analysis using logistic regression is used to analyze the tendency of the factors that determine the efficiency level of regional owned rural banks in Indonesia. This study found that Equity to Total Asset Ratio (EAR) and Total Assets had a positive and significant effect, while Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR) factor has no significant effect on the efficiency level of regional owned rural banks in Indonesia. Therefore, in improving the performance of regional owned rural banks in Indonesia, it is necessary to have the role of local governments in capital participation and discipline in the disbursement of funds selectively to debtors.Keywords: Regional Owned Rural Banks, Efficiency Level